Indonesia and World Trade Organization’s Prohibtion on Fisheries Subsidies: Finding a Breakthrough - Gea, Gita Venolita Valentina; Krustiyati, Atik; Veronica, Shierren (Reformasi Hukum, 2025)
Fishermen have long been a vital part of coastal communities, especially in developing countries like Indonesia. However, the recent prohibition of fisheries subsidies by the World Trade Organization (WTO) has raised significant legal and economic concerns. This article aims to examine the implications of the WTO’s Agreement on Fisheries Subsidies for Indonesia and explore potential legal strategies to reconcile international obligations with national interests. Using a normative juridical method, this study analyzes the provisions of the WTO agreement, particularly the eight types of prohibited subsidies, and their impact on Indonesia’s small-scale fisheries sector. The findings indicate that a sudden termination of these subsidies may harm the livelihoods of traditional fishermen and disrupt coastal economies. This situation presents a legal and diplomatic paradox: Indonesia must comply with global trade rules while safeguarding the welfare of its people. As a solution, Indonesia should leverage international negotiations and legal mechanisms to advocate for flexibilities or special treatment for developing countries. In conclusion, while the WTO agreement aims to prevent overfishing and promote sustainability, its implementation must be carefully balanced to avoid adverse effects on developing nations. Indonesia must therefore find a legal and diplomatic breakthrough to protect both its obligations and its national interests.